Comparative evaluation of initially static and motile semen ejaculates from Friesian and Murrah buffalo bulls for physico-morphological, biochemical, enzymatic and mineral constituents of seminal plasma* - DHAMI, A J; SAHNI, K L; MOHAN, GREESH; TRIPATHI, R P (The Indian Journal of Animal Sciences, 2013)
The occurrence of static ejaculatcs averaged 7.82 and 11.21% based on 115 and 107 collections from 3 Friesian and 3 Murrah bulls respectivelyo. The revivul rate of static ejaculates was significantly lower in Friesian than in Murrah. The values in static ejaculates for spenn density, motility, concentralion perml und per ejaculate uno live sperm per cent were significantly lower ami those of pH and dead/abnormal spennwere higher than in the motile ejaculates. The profiles of enzyme GOT, GPT, AKP, ACP and LDH, although apparently lower in static than in motile samples, did not differ signiricantly in either of the species. Biochemical and mineral constituents were also more in static than in motile ejaculates of both the species. However, only the level of protein, cholesterol, and acid-soluble and ester phosphates differed significantly between static and molile samples in Murrah. In Friesian, the total protein and copper contents weresignificanlly lower and the chloride and zinc contents were higher in stalic than in motile ejaulates. Levels of frocLuse, inorganic phosphate, sodium, potassium, iron and manganese did not differ significantly between semen types in either of the species. Further, the overall means of ejaculate voiume, dead/abnormal spenn. GOT, protein, chloride and sodium were significantly (P